Barriers to salpingectomy for permanent contraception: A qualitative study with obstetricians and gynaecologists. (23rd September 2021) - Obermair, Helena M.; Muir, Georgia; Gard, Gregory B.
Abstract : Consideration of risk‐reducing bilateral salpingectomy has been recommended instead of tubal occlusive procedures for female sterilisation due to the role of the Fallopian tubes in the aetiology of serous ovarian malignancies. This study identified barriers to performing salpingectomy for permanent contraception. Twenty‐two semi‐structured interviews were conducted with Australian gynaecologists, and transcripts analysed qualitatively. Barriers to performing bilateral salpingectomy included: (a) patient factors (younger age and risk of regret); (b) operative complexity and complications (particularly risk of bleeding); (c) surgeon factors (lack of awareness of guidelines supporting salpingectomy; less comfort with laparoscopic surgery); and (d) practical system challenges (including cost and equipment availability).